Training Using Circuit Style and Its Effect On Some Enzymes and Lactic Acid Accumulation In Freestyle Wrestlers In Iraq - Sami, Fahad; Saleh, Rafea (Journal of Physical Education, 2019)
The research aim at designing a training program using circuit style as well as identifying the values of LDH and CPK enzymes, lactic acid accumulation. The researchers used the experimental method. The subjects were (14) advance freestyle wrestlers. The training program was applied for (8) weeks with 3 training sessions per week. The data was collected and treated using proper statistical operations to conclude the success of the training program in developing the levels of LDH, CPK, and lactic acid. Finally the researchers recommended using other training methods with other suitable intensities and volumes